Manajemen Event Talk Show Virtual Oleh Pt Pilihanmu Indonesia Jaya - Riqqah, Aisyah Zahra; Akbar, Djuni; Rudatin, Christina L. (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2024)
The process of choosing a major plays a very important role in shaping the career and academic development of prospective students. Geographical factors and limited physical access can be an obstacle for prospective students outside the region to attend events held in person. In the digital era, technology and education have become a major unity as a tool of the present through the use of digital platforms. The talk show titled